Development of IBT Based Two-Tier Higher Order Thingking Skills (HOTS) Test Instruments on Acid-Base Titration Materials for SMA/MA Students - Shiva Atika Suri; Andromeda Andromeda (Entalpi Pendidikan Kimia, 2022)
This research is a development research that aims to produce a two-tier Higher Order Thinking Skills (HOTS) test instrument based on IBT on a valid and reliable acid-base titration material. This research is a research and development (R&D) research using the Treagust model which has 3 stages, namely determining content, obtaining information about students regarding the developed instrument, and developing a diagnostic test. Content validity analysis using the CVR method and construct validity using Aiken V. The CVR value of content validity which consists of stimulus questions, questions, answers to questions and reasons for questions is 1, the results of content validity in the form of statements of knowledge of prepositions and concept maps are 1, then construct validity is 95% from the material aspect, 95% from the presentation aspect, 97% of the language aspect, and 98% of the additional rule. The reliability value of this test instrument is 0.89 first tier and 0.90 second tier. The results show that the developed test instrument is valid and has high item reliability.